Woman Suffrage By Federal Constitutional Amendment - Catt, Carrie Chapman, 1859-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"Woman Suffrage By Federal Constitutional Amendment" by Carrie Chapman Catt is a historical account written during the early 20th century. The work discusses the necessity of introducing a federal amendment to grant women the right to vote in the United States, highlighting the struggles and the contrasting experiences of different groups regarding suffrage. The opening of the text sets a context for the discussion by firmly establishing the author's right to advocate for a constitutional amendment. Catt discusses the background of the women$1 (Bs suffrage movement, mentioning significant attempts made to gain voting rights since the amendment's introduction in Congress in 1878. She outlines the contrast between the ease with which many men have gained voting rights and the hurdles faced by women, emphasizing the injustice of disenfranchising educated, capable women while allowing unqualified groups of men to vote. Catt's introductory remarks lay the groundwork for her argument by detailing both historical precedence in other nations granting women's suffrage and the essential need for a unified federal approach to secure voting rights nationwide. (This is an automatically generated summary.)s
Release date is 2004-10-01
Produced by Audrey Longhurst, S.R.Ellison and the Online Distributed Proofreading Team
Keywords: Women -- Suffrage -- United States